1979
DOI: 10.1111/j.1365-2133.1979.tb05577.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma complement and histamine changes in atopic dermatitis*

Abstract: Fifteen patients with atopic dermatitis were investigated to evaluate the total of complement and histamine. In five patients total serum complement haemolytic activity (CH50) was significantly decreased as was the haemolytic activity of complement components C2 (C2H50) and C3 (C3H50). By counter immunoelectrophoresis split products of C3 were detected. There was no evidence for alternative pathway activation or the presence of an activator of the alternative pathway. In three patients plasma histamine concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 39 publications
(18 reference statements)
0
13
1
Order By: Relevance
“…However, assessment methods are far from being standardized, and therapeutic studies are often difficult to interpret. Efforts have been done recently to classify patients in groups of severity [2][3][4] and to estab lish simple and reliable assessment methods [5][6][7][8][9][10][11]. Var iants of the scoring system proposed in psoriasis (PASI score [12]) have been published [13.…”
Section: Introductionmentioning
confidence: 99%
“…However, assessment methods are far from being standardized, and therapeutic studies are often difficult to interpret. Efforts have been done recently to classify patients in groups of severity [2][3][4] and to estab lish simple and reliable assessment methods [5][6][7][8][9][10][11]. Var iants of the scoring system proposed in psoriasis (PASI score [12]) have been published [13.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in creased amounts of histamine have been found to be released in vitro [28,30] and measured in the plasma of severely atopic patients [9,29,34]. In our study we ob served no significant correlation between the intensity of the clinical symptoms of dermatitis nor serum IgE concentration to the amount of change in intracellular cyclic nucleotides.…”
Section: Discussionmentioning
confidence: 34%
“…Ab normalities in the serotonin response have been described in patients with atopic der matitis [25,29]. Platelets represent the main reservoir of serotonin in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, complement activation has been demonstrated in plasma and skin of patients with atopic dermatitis [47,[49][50][51][52], Apart from the /^-adrenergic deficiency atopic patients seem to have an increased sensitivity to «-adrenergic and cholinergic stimuli in vivo and in vitro [27,33,43], both of them favouring the release of va soactive mediators.…”
Section: Release Of Vasoactive Mediatorsmentioning
confidence: 99%
“…Indeed, it was shown that patients with atopic dermatitis show elevations of plasma and skin histamine concentrations [43,47,55,56].…”
Section: Psychological Influencementioning
confidence: 99%